PENGAWASAN KESELAMATAN JALAN PADA ANGKUTAN KOTA - Margaretha Aprilia Rosa Br Sihombing; Asima Yanty Siahaan (Jurnal Kebijakan Publik, 2024)
This research aims to determine and describe supervision of the feasibility and safety of city transportation in the city of Medan. The research method used is a descriptive research method with a qualitative approach. Data collection techniques were carried out by means of interviews, observation and documentation. The data obtained was then analyzed qualitatively by reviewing all the data that had been collected and supported by the results of interviews using the Handoko supervision indicator approach, which stated that supervision can be seen through determining implementation standards, determining implementation measurement, measuring activity implementation, comparison with evaluation standards, and taking corrective action. The results of this research indicate that supervision of roadworthiness and road safety in city transportation in the city of Medan is not yet fully operational. This can be seen from the large number of city transport that does not carry out motor vehicle testing and the high number of vehicles that are not roadworthy in 2023, as many as 60,948 vehicles, but 9,198 of them include city transport. Then supervision is not yet optimal due to inadequate testing equipment and testing equipment. damaged and calibrated and the Transportation Department's lack of firmness in carrying out raids so that vehicles still pass the raid. Another problem in the field is that there are public transportation drivers who do not comply with carrying out periodic tests and repairing damaged city transportation due to the condition of the vehicle.